Case report: Pylorus-preserving pancreatoduodenectomy for focal congenital hyperinsulinism in a 5-month-old baby - Spagnoletti, Gionata; Larghi Laureiro, Zoe; Maria Fratti, Alberto; Maiorana, Arianna; Garganese, Maria Carmen; Pizzoferro, Milena; Dionisi-Vici, Carlo; Spada, Marco (Frontiers in Surgery, 2023)
Background: In focal congenital hyperinsulinism (CHI), surgery is the gold standard of treatment, even for lesions localized in the head of the pancreas. We report the video of the pylorus-preserving pancreatoduodenectomy performed in a five-month-old child with focal CHI. Operative technique. Baby was placed in the supine position with both arms outstretched to the up. After transverse supraumbilical incision and mobilization of ascending and transverse colon, exploration and multiple biopsies of the tail and the body of the pancreas ruled out multifocality. Pylorus-preserving pancreatoduodenectomy was performed according to the following steps: extended Kocher maneuver, followed by retrograde cholecystectomy and common bile duct isolation; division of the gastroduodenal artery and of the gastrocolic ligament; division of the duodenum, Treitz ligament and jejunum; transection of the pancreatic body. The reconstructive time was with: pancreato-jejunostomy; hepaticojejunostomy; pilorus-preserving antecolic duodeno-jejunostomy. The anastomoses were accomplished with synthetic absorbable monofilament sutures; two drains were placed close to the biliary and pancreatic anastomoses and to the intestinal anastomosis, respectively. Total operative time was 6 hours, with no blood loss and/or intra-operative complications, immediate normalization of blood glucose levels and discharge from surgical ward 19 days after surgery. Conclusions Surgical treatment of medical unresponsive focal forms of CHI is feasible in very small children: it is mandatory to refer the baby to a high-volume centre for a multidisciplinary management involving hepato-bilio-pancreatic surgeons and experts in metabolic disease.